Internet Addiction: The Problem and Treatment - Kuss, Daria J. (Addicta: The Turkish Journal on Addictions, 2016)
Internet Gaming Disorder has recently been included in the appendix of the most recent edition of the Diagnostic and Statistical Manual for Mental Disorders (DSM-5) as a condition which requires further research in order to be incorporated in future iterations of the manual. This suggests the research and clinical communities are becoming increasingly aware of a potential mental health concern. This paper will provide brief insight into the issues of Internet and gaming addiction and will then present results of contemporary treatment research. The results indicate no gold standard exists to measure Internet addiction with high sensitivity and specificity, which is compounded by using dissimilar cut-offs across studies for the same assessment tool. To overcome this diagnostic issue, a diagnosis of Internet addiction would significantly benefit from the inclusion of a structured clinical interview administered by a trained professional, and this would help in the elimination of false positives and false negatives in the context of diagnosis. Citation: Kuss, D. J. (2016). Internet addiction: The problem and treatment. Addicta: The Turkish Journal on Addictions, 3, 185‒192. http://dx.doi.org/10.15805/addicta.2016.3.0106